Performance of a Full-Scale Anaerobic Digestion on Bakery Wastewater Treatment : Effect of Modified Distribution System - Hanny Vistanti; Rizal Awaludin Malik; Aris Mukimin (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
The effectiveness of a full-scale anaerobic digestion pretreatment was evaluated and the effect of wastewater distribution system was determined on the performance of bakery wastewater (BW) treatment. The BW was fed to 3 series of anaerobic compartments as the main degradation process. The distribution system of first compartment was modified and circulated to enhance contact and efficiency. While the effluent of last compartment was partly returned to the first compartment as an external circulation and the other part was further processed in activated sludge under aerobic conditions. The overall system was able to remove chemical oxygen demand (COD), total suspended solids (TSS), and biochemical oxygen demand (BOD) up to 97.7%, 99.7%, and 99.6%, respectively, at maximum organic loading rate of 6.3 kg COD/m3day. High removal of pollutants indicated that modified distribution of circulation is advantageous to the BW treatment